Guinea : First Review of the Arrangement Under the Three-Year Extended Credit Facility, Financing Assurances Review, and Request for Modification and for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2018)
The Guinean economy is growing at a faster than anticipated pace on the back of buoyant mining activity. The growth momentum is expected to continue, with real growth at about 6 percent in 2018 and over the medium term. However, risks of instability are heightened by the current electoral cycle.